2016
DOI: 10.1002/jat.3422
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin biomarkers in hair may facilitate long‐term exposure studies

Abstract: Aflatoxins are highly toxic fungal metabolites produced by some members of the Aspergillus species. They are low molecular weight lipophilic compounds that are easily absorbed from the gastrointestinal tract. They contaminate most staple foods, including maize, peanuts, peanut butter and sorghum mainly in the tropics where hot and humid conditions promote fungal growth. Absorbed aflatoxins are metabolized by the cytochrome P450 enzyme system in the liver into toxic metabolites. Aflatoxin B (AFB) is the most to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…The measurement of the AFM 1 in urine samples indicated recent exposure of aflatoxin AFM 1 within the preceding 24 h. Since this biomarker is short-lived, and its measurement in urine samples may vary from day to day as well as the dietary intake of the individual, it may not be suitable for assessing long-term aflatoxin exposure. Thus, it is suggested to use other biological samples such as serum AFB 1 -lysine adduct and hair, which can represent the long-term effect of aflatoxin exposure [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the AFM 1 in urine samples indicated recent exposure of aflatoxin AFM 1 within the preceding 24 h. Since this biomarker is short-lived, and its measurement in urine samples may vary from day to day as well as the dietary intake of the individual, it may not be suitable for assessing long-term aflatoxin exposure. Thus, it is suggested to use other biological samples such as serum AFB 1 -lysine adduct and hair, which can represent the long-term effect of aflatoxin exposure [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The half-life for AFB1 in four human volunteers was 64.4 h [143]; although it should be taken into account that authors did not discriminate between AFB1 and its metabolites or conjugates [144]. For AFB1-lys, and due to lysine stability in human serum, a half-life of 2-3 months was estimated by Mupunga et al (2016) [145]. These authors also stated that AFM1 has a short half-life, though no value was indicated.…”
Section: Risk Characterizationmentioning
confidence: 99%
“…The search for AFB1 biomarkers in hair and nail samples is relevant, as it may indicate exposure that has occurred for a longer time (Mupunga et al, 2017).…”
Section: Aflatoxinsmentioning
confidence: 99%